Finite element analysis of fractured tibia treated with ZESPOL stabilizer - Rusiński, Eugeniusz; Wall, Andrzej; Sobolewski, Roman (Computer Assisted Methods in Engineering and Science, 1996)
Some aspects of applying the external stabilization method to the treatment of selected cases of tibia fractures make the subject of this paper. ZESPOL, used as an external stabilizer, was selected from among many other methods. In order to define the state of deformations and stresses existing in a fractured tibia stabilized with ZESPOL, an unconventional quantitative model was prepared. Finite element analysis was applied to the strength analysis of the whole system. Some final results and computations are presented